The Functional Movement Screen as an injury prediction tool for German physical education and exercise science students: a prospective cohort-study - Schweda, Simone; Leyhr, Daniel; Krauß, Inga (physioscience, 2021)
Background Several studies have evaluated the applicability of the Functional Movement Screen (FMS) as a screening tool for injury prediction. However, only few studies investigate gender differences for FMS as a screening tool for female and male college students.Objective To evaluate gender differences in FMS single items and the overall score. In addition, the applicability of FMS as a diagnostic tool for injury prevention of German exercise students will be investigated.Method N = 99 college students performed an FMS at the beginning of the semester. Injuries were recorded for the entire term. Gender differences of FMS single items were assessed using the Mann-Whitney-U-Test. Differences in injury prediction were calculated using logistic regression. If the model was statistically significant, diagnostic accuracy was calculated using receiver operating characteristic (ROC) curves and the area under the curve (AUC). The Youden index was used to identify a cut-off score. 2 × 2 contingency tables, sensitivity and specifity, positive/negative predictive values, and likelihood ratios were assessed.Results There were significant gender differences for Deep Squat, Shoulder Mobility, Trunk Stability Push Up, and Active Straight Leg Raise. The logistic regression showed that the composite score was statistically significant in clarifying the model for females (p = 0.005, RN2 = 0.14), but not for males (p = 0.18, RN2 = 0.04). The ROC curve indicated acceptable injury prediction in females (AUC: 0.66, p = 0.02) and poor injury prediction in males (AUC: 0.40, p = 0.19). The cut-off score of ≤ 16 for females resulted in a sensitivity of 63 % and specificity of 54 %. No cut-off score was calculated for males.Conclusion Females performed better on flexibility items, while males scored higher on strength exercises. Results of the study indicate low predictive accuracy. Therefore, no solid recommendation can be made for the use of the FMS as an injury screening tool for either female or male German exercise science students.
Keywords: screening; injury prevention; college student; risk factor